2015
DOI: 10.1007/s00360-015-0935-3
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 6 from the Antarctic emerald rockcod: molecular characterization of its response to warming

Abstract: In the present study, we describe the purification and molecular characterization of two peroxiredoxins (Prdxs), referred to as Prdx6A and Prdx6B, from Trematomus bernacchii, a teleost widely distributed in many areas of Antarctica, that plays a pivotal role in the Antarctic food chain. The two putative amino acid sequences were compared with Prdx6 orthologs from other fish, highlighting a high percentage of identity and similarity with the respective variant, in particular for the residues that are essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…These results indicate that the protein was over-oxidized at position C47 by oxidant treatment allowing it to react with the antibody but that the disulfide bond at C91 was not affected by treatment with the oxidant. This mechanism for dimerization at C91would not occur in Prdx6 proteins that contain a single cysteine, e.g., rat or bovine Prdx6 (3, 29), and was not further investigated as it is unlikely to be physiologic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the protein was over-oxidized at position C47 by oxidant treatment allowing it to react with the antibody but that the disulfide bond at C91 was not affected by treatment with the oxidant. This mechanism for dimerization at C91would not occur in Prdx6 proteins that contain a single cysteine, e.g., rat or bovine Prdx6 (3, 29), and was not further investigated as it is unlikely to be physiologic.…”
Section: Resultsmentioning
confidence: 99%
“…Further, crystallization of human Prdx6 demonstrated that dimerization of the protein occurs in the absence of C91 and without disulfide formation (17). There was evidence of covalent dimerization in some experiments, but the fraction of total Prdx6 that was covalently dimerized was minor and involved a Cys residue (C91) that is present in human Prdx6 but is not conserved in the Prdx6 proteins of other species that have been sequenced (14, 29, 35). …”
Section: Discussionmentioning
confidence: 99%
“…Expression of SmPrx6 increased rapidly in S. maindroni and peaked at 6 h post-stimulus (3.72-fold; p \ 0.05) before declining and eventually returning to control levels. This indicates that SmPrx6 may play a major role as an antioxidant protein to protect organisms from excessive ROS following thermal stress (Tolomeo et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Prx6 has a single conserved catalytic cysteine residue in the N-terminal catalytic motif (PVCTTE) that is responsible for the peroxidase activity (Manevich and Fisher 2005). Evidence suggests Prx6 is distributed in all major tissues that are sensitive to oxidative stress (Manevich and Fisher 2005), and its expression is induced by stimuli such as bacteria (Zheng et al 2010), viruses (Nikapitiya et al 2009), pathogen-associated molecular patterns (PAMPs) (De Zoysa et al 2012), chemicals (Wang et al 2008), thermal stress (Park et al 2008;Tolomeo et al 2016) and environmental pollutants (David et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation